ANALISIS PENERAPAN ANGGARAN BERBASIS KINERJA DALAM MENINGKATKAN KUALITAS LAPORAN REALISASI ANGGARAN BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN MUSI BANYUASIN - Ifrah Juli Dwiyanti; Jumania Septariani (Surplus: Jurnal Riset Mahasiswa Ekonomi, Manajemen, dan Akuntansi, 2021)
This study aimed to measure the implementation of performance-based budgeting and the quality of budget realization reported at the Regional Financial and Asset Management Agency (BPKAD) Musi Banyuasin Regency. The method used in this study was a qualitative and quantitative analysis technique by describing the reality of situation or an object in the form of a description based on information from parties related to the study. The data analysis used in this study was an income performance analysis, spending growth analysis and conformity budget analysis. Musi Banyuasin Regency has implemented performance-based budgeting so well. This could be seen from the LKJIP which stated that performance achievement was measured by comparing performance realization with performance targets achieved. Based on the ratio of financial independence, Musi Banyuasin Regency was still very low. It was included in a consultative relationship pattern which means that the role of the central government was more dominant than the regional government. This was indicated by the independence ratio of Musi Banyuasin Regency from 2016-2019, which was 50%. However, in total, Musi Banyuasin Regency was said to have a good income performance because it was able to earn income that exceeds the budgeted amount.